Radio detection of meteors and other near-Earth targets - Zhang, Xiang (Curtin University, 2018)
Meteors and other near-Earth targets have always been under surveillance due to the risk of impacts with ground and space assets. In this thesis, we report the investigation of intrinsic radio emission from meteors using the Murchison Widefield Array (MWA), and the detected reflection of FM broadcasting signals from satellites. We also discussed ground-based radar detection of near-Earth asteroids and generated models from delay-Doppler images.